Supporting the improvement of air quality management practices: The "FAIRMODE pilot" activity. (1st September 2019) - Pisoni, E.; Guerreiro, C.; Lopez-Aparicio, S.; Guevara, M.; Tarrason, L.; Janssen, S.; Thunis, P.; Pfäfflin, F.; Piersanti, A.; Briganti, G.; Cappelletti, A.; D'Elia, I.; et al.
Abstract: This paper presents the first outcomes of the "FAIRMODE pilot" activity, aiming at improving the way in which air quality models are used in the frame of the European "Air Quality Directive". Member States may use modelling, combined with measurements, to "assess" current levels of air quality and estimate future air quality under different scenarios. In case of current and potential exceedances of the Directive limit values, it is also requested that they "plan" and implement emission reductions measures to avoid future exceedances. In both "assessment" and "planning", air quality models can and should be used; but to do so, the used modelling chain has to be fit-for-purpose and properly checked and verified. FAIRMODE has developed in the recent years a suite of methodologies and tools to check if emission inventories, model performance, source apportionment techniques and planning activities are fit-for-purpose. Within the "FAIRMODE pilot", these tools are used and tested by regional/local authorities, with the two-fold objective of improving management practices at regional/local scale, and providing valuable feedback to the FAIRMODE community. Results and lessons learnt from this activity are presented in this paper, as a showcase that can potentially benefit other authorities in charge of air quality assessment and planning. Highlights: Air quality is still a challenge in various areas in Europe. FAIRMODE provides methodologies and tools for supporting air quality improvement. Specifically, a new FAIRMODE initiative for better management practices has been recently launched. The initiative provides a "live tutorial" to interested authorities. First results on improved emission inventories and concentrations are presented.